A remarkable new species of ranid (Anura: Ranidae) with phytotelmonous larvae from Mount Harriet, Andaman Island - Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 1998)
A new species of ranid, tentatively assigned to the genus Rana (sensu Boulenger, 1920) is described from Mount Harriet National Park, South Andaman Islan, India. The new species, R.charledarwini, is diagnosed by the folllowing suite of characters: tympanum large, exposed; lingual papilla absent, digit tips swollen but not dilated, lacking circummarginal grooves; ova pigmented, relatively numerous; the single adult male known smaller than two adult females and shows a median vocal sac and smooth nuptial pads on upper surface of first finger.